Retiree migration and intergenerational conflict - Mehmet S. Tosun (IZA World of Labor, 2015)
With the aging of populations, particularly in more developed countries, retirees are becoming a politically influential group. Government budgets have been feeling the strain on social insurance, health care, and other programs that benefit the elderly. Yet spending on these programs has often come at the expense of other programs such as education, which benefit primarily the younger population. Attracting retirees has been viewed as an important avenue of economic development, with positive impacts on revenue and expenditure. However, it can also have a negative impact on education spending potentially resulting in intergenerational fiscal conflict.
Keywords: H52; H72; J11; J14; J26; J61; 330; population aging; retiree migration; intergenerational conflict; education spending